Diagnosis of Myasthenia Gravis - Blaes, Franz (Neurology International Open, 2018)
Myasthenia gravis is an autoimmune disorder of the neuromuscular junction. The diagnosis of myasthenia gravis (MG) is based on clinical features, combined with neurophysiological and immunological parameters. Autoantibodies against the nicotinic acetylcholine receptor are the main finding in about 80% of the patients. More recently, autoantibodies against muscle-specific kinase (MuSK) and lipoprotein receptor-associated protein 4 (LRP4) have been identified in a subset of MG patients. Additionally, anti-titin autoantibodies can point to an underlying thymoma in younger MG patients. Neurophysiological examination includes a repetitive stimulation to detect a possible decrement as the electrical correlate of pathological muscle fatigability. Single-fiber electromyography can identify neuromuscular transmission disturbances in otherwise unclear cases.
Keywords: myasthenia gravis; autoantibodies; neurophysiology